The Secret Explorers and the missing scientist - King, SJ (King, SJ. Secret Explorers, 2021)
Meet the Secret Explorers - a band of brainiac kids from all around the world. Everyone in this group of young experts has a speciality, from outer space to dinosaurs, and each story follows a character who gets chosen for a "secret exploration". In this fun, fact-filled children's book, engineering expert Kiki and Connor the marine biologist are sent on a mission to the Arctic. There they discover a research vessel studying the effects of climate change that has become trapped in the sea ice. To make matters worse, one of the ship's scientists who went to find help at a nearby research station hasn't returned. It's up to the Secret Explorers to find the scientist, free the ship, and save the day! Kids will love turning the pages to find out if the Secret Explorers manage to succeed in their mission!